Brushables: Example‐based Edge‐aware Directional Texture Painting. (15th October 2015) - Lukáč, M.; Fišer, J.; Asente, P.; Lu, J.; Shechtman, E.; Sýkora, D.
Abstract: In this paper we present Brushables—a novel approach to example‐based painting that respects user‐specified shapes at the global level and preserves textural details of the source image at the local level. We formulate the synthesis as a joint optimization problem that simultaneously synthesizes the interior and the boundaries of the region, transferring relevant content from the source to meaningful locations in the target. We also provide an intuitive interface to control both local and global direction of textural details in the synthesized image. A key advantage of our approach is that it enables a "combing" metaphor in which the user can incrementally modify the target direction field to achieve the desired look. Based on this, we implement an interactive texture painting tool capable of handling more complex textures than ever before, and demonstrate its versatility on difficult inputs including vegetation, textiles, hair and painting media.